Śrī Vidyāraṇyaviracita Śrī Pañcadaśī : Vedānta prakriyāno mukha grantha, tenuṃ Gujarātīmāṃ bhāshāntara Candrakānta vivaraṇa ane Svāminā jīvanavrtta sahita - Mādhava, d. 1386 (Naṭavaralāla Īcchārāma Desāī, 1933)
Compendium of the Advaita philosophy and its commentary Candrakānta vivaraṇa in Gujarati.